A Structural, Cognitive, and Behavioral Model for Error Analysis of Group B Streptococcus Prophylaxis in Pregnancy - Robert E. Murphy; Jane C. Ibekwe; Stella I. Ibekwe; Jerrie S. Refuerzo (Thieme Medical Publishers, Inc., 2022)
The objective of this study was to develop a structural-cognitive-behavioral model for error analysis of group B streptococcus (GBS) prophylaxis failure, classify delivery cases into this model, and examine compliance with treatment guidelines. A retrospective, cohort study was conducted of women with liveborn pregnancies greater than 24 weeks in April 2018 at a single hospital. We created a structural-cognitive-behavioral model of five assessments for adherence to GBS prophylaxis guidelines and then classified these into four distinct error stages. A descriptive analysis was performed to determine if the pregnancy had a perfect process, a GBS prophylaxis failure, or a fortuitous outcome. There were 313 women who met the study criteria. The rate of GBS positive was 12.8%, negative 37.4%, and unknown 49.8%. The most common errors were cognitive perception errors related to incorrectly documenting GBS status, 57.7% (N = 79). Of these errors, 15.2% (N = 12) led to GBS prophylaxis failure. Perfect outcomes occurred in 62.7% (N = 196) women, GBS prophylaxis failure occurred in 13.7% (N = 43), and fortuitous outcomes occurred in 23.6% (N = 74). In our study, we were able to identify structural, cognitive, and behavioral errors that contribute to GBS prophylaxis failures. In other cases, these errors may contribute to fortuitous outcomes.